The latest methods of treating type 1 diabetes, improving patients’ quality of life – a review of the literature - Bąk, Dominika (Journal of Education, Health and Sport, 2025)
Introduction: Type 1 diabetes is a chronic autoimmune disease characterized by destruction of pancreatic β cells and resultant absolute insulin deficiency. Despite advances in insulin delivery systems and glucose monitoring, patients remain at risk for severe acute and chronic complicationsConsequently, new approaches are being intensively developed, including cell-, gene-, and immunology-based therapies. Aim of the Study: The purpose of this study is to investigate new therapies used in type diabetes that may reduce the need for exogenous insulin. Materials and Methods: An analysis of papers available in PubMed was performed. Basic results: In recent years, many modern treatment methods have been studied, including the use of anti-CD3 antibodies. In November 2022, teplizumab (an anti-CD3 antibody) was approved as a drug that, by slowing the autoimmune destruction of pancreatic β cells, prolongs endogenous insulin production and delays the need for intensive insulin therapy. Another intensively investigated approach is pancreatic islet transplantation. The latest research results show that pancreatic islet transplantation improves glycemic control, prevents severe episodes of hypoglycemia, and makes some patients insulin-independent. In addition, results from 2024 on the first-ever transplantation of pancreatic islets derived from chemically induced pluripotent stem cells (CiPSCs) suggest that this treatment may be a personalized therapeutic strategy for patients with type 1 diabetes. However, further studies with a larger number of patients and longer follow-up periods are needed to assess the long-term safety and efficacy of this method. Conclusion: None of the existing therapies for type 1 diabetes is entirely optimal. Rapid scientific advances and emerging stem cell transplantation technologies offer patients hope for improved quality of life through better glycemic control, prevention of severe hypoglycemic episodes, and insulin independence.